MIDWIFERY CARE MANAGEMENT OF MR. T WITH INTRACRANIAL TUMOR AT RSU HAJI MEDAN - Mariati, Djanius; Fitri, Annisa; Tafonao, Marlina; Sianipar, Priska Estetika; Simanullang, Ester (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Intracranial tumors are abnormal tissue growths inside the skull that can increase pressure in the brain and affect neurological function. Patients often experience headaches, visual disturbances, weakness of the arms and legs, seizures, and decreased consciousness. Delayed diagnosis and lack of understanding about the disease can worsen the patient's condition. Therefore, comprehensive care is needed to support recovery and improve quality of life. Objective: This study aimed to describe the implementation of midwifery care management for a patient with an intracranial tumor at RSU Haji Medan in 2025. Methods: This study used a descriptive case study approach. Data were collected through interviews, direct observation, physical examination, neurological assessment, monitoring of vital signs, and review of medical records. Midwifery care was provided using Helen Varney’s 7-step management approach, and the data were analyzed descriptively. Results: The patient experienced persistent headache, weakness of the arms and legs, visual disturbances, and fatigue. The care provided included monitoring of neurological status and vital signs, health education, psychological support, and collaboration with other healthcare professionals. Evaluation showed improvement in neurological status, reduced symptoms, stable physical condition, and better understanding of the disease and treatment process. Conclusion: Comprehensive midwifery care management helps maintain patient stability, improve neurological outcomes, and support recovery. Continuous assessment, patient education, psychological support, and collaboration with healthcare professionals are important in caring for patients with intracranial tumors.